PERAN LITERASI KEUANGAN SEBAGAI VARIABEL MEDIASI DALAM PENGAMBILAN KEPUTUSAN INVESTASI PADA GENERASI Z : UJI TERHADAP BIAS-BIAS PERILAKU - Anggriani, Yeni; Anwar Azazi; Wenny Pebrianti; Uray Ndaru Mustika (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to investigate the role of financial literacy as a mediator in investment decision making by Generation Z in Indonesia, especially on the influence of behavioral biases such as overconfidence, representativeness, and availability. Using a quantitative cross-sectional approach and purposive sampling technique, this study involved 257 Generation Z respondents who had investment experience. Data were obtained through an online questionnaire and analyzed using path analysis and the Sobel test. The results show that financial literacy significantly mediates the relationship between behavioral biases and investment decisions. Overconfidence and availability have a positive effect on financial literacy, while representativeness has an indirect effect through investment decisions. These findings emphasize the importance of financial literacy in minimizing the impact of behavioral biases and encouraging more rational investment decision making among Generation Z.